Discover the best answers at Westonci.ca, where experts share their insights and knowledge with you. Discover in-depth answers to your questions from a wide network of experts on our user-friendly Q&A platform. Discover in-depth answers to your questions from a wide network of professionals on our user-friendly Q&A platform.

If f(x) = 3x – 1 and g(x) = x², then what is (fºg)(x)?


Sagot :

Answer:

3x^2-1

Step-by-step explanation:

Answer:

f(x) = 3x – 1 and g(x) = x²

Putting the value of g(x) in f(x), we get

(fog)(x)= f{g(x)}= f(x²) = (3x²-1)

(3x²-1) is the right answer.